Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 72. Beitrag. Coleoptera: Histeridae. - Thérond, Jean (Contributions to Entomology = Beiträge zur Entomologie, 1969)
An evaluation of the Histeridae of Albania is presented. The material on which the study is based (a total of 115 individuals of 26 species) was gathered by the expedition to Albania by Deutsches Entomologisches Institut (75 individuals of 15 species), by Bischoff (26 individuals of 10 species, at the Zoological Museum in Berlin) and by Grebenscikov (14 individuals of 6 species, at Deutsches Entomologisches Institut). Since to our knowledge only 5 of the species discussed here had been previously recorded from Albania, 21 species must be regarded as first finds in the fauna of that country. Now there are 29 species of this family known from the territory of the People's Republic of Albania.